New hepatitis C therapies for special patient populations. (22nd January 2016) - Soriano, Vincent; Labarga, Pablo; de Mendoza, Carmen; Fernández-Montero, José V; Esposito, Isabella; Benítez-Gutiérrez, Laura; Peña, José M; Barreiro, Pablo
ABSTRACT: Introduction : Chronic hepatitis C virus (HCV) infection has become a curable disease. More than 90% sustained virologic response rates have been obtained with 8–24 weeks of treatment with distinct combinations of direct-acting antivirals (DAA) in most registration trials. However, outcomes in real-world patients tend to be lower and treatment of special patient populations is often challenging. Areas covered : We address the treatment of chronic hepatitis C with DAA in major special patient populations, such as HIV-positive persons, transplant recipients, patients with advanced cirrhosis, renal insufficiency, hepatitis B or D coinfection, injection drug users (IDUs) and prior DAA failures. Expert opinion : Drug interactions between DAA and medications given to persons with HIV infection or transplant recipients can result in treatment failure and adverse events. Severe organ dysfunction as in kidney insufficiency or decompensated cirrhosis may lead to DAA overexposure and toxicities. Dysfunctional social circumstances and behavior are associated to poor drug adherence and increased risk for HCV re-infection in active IDUs. Finally, DAA response might be impaired by viral interference in patients with hepatitis B or D coinfection or drug resistance in HCV either at baseline or after prior DAA failures.